Timing and prognostic factors of tuberculosis treatment interruption - Suliman, Qudsiah; Md Said, Salmiah; Lim, Poh Ying (Universiti Putra Malaysia Press, 2019)
The global Tuberculosis epidemic (TB) poses a significant public health threat. While the consequences of TB treatment interruption are indisputable, the knowledge about the timing and prognostic factors of TB treatment interruption is fundamental. Despite a considerable amount of evaluation, the timing and prognostic factors of TB treatment interruption have been inconsistently identified from one study to another. Therefore, this study aimed to examine the evidence obtained from published literature on the timing and prognostic factors of TB treatment interruption at different points of the treatment course. In this review, three databases namely Pubmed, Scopus, and Science Direct were used to identify articles published from January 2003 to February 2018. This was based on the inclusion criteria and keywords including ‘default’, ‘survival time’, ‘tuberculosis’, and ‘treatment interruption’. The nine selected studies were prospective and retrospective cohort studies conducted in developing countries. The diversity of the study’s participants and TB treatment interruption definition were allowed, thus delineating a heterogeneous finding. This review suggests that the interruption predominantly occurred during the maintenance phase of treatment course. Despite the finding, a considerable gap in understanding the prognostic factors at different time points of TB treatment interruption was elicited. The heterogeneity across the studies may limit the inferences and warrant further evaluation. In essence, the time-related information should be integrated into framing impactful public health strategy, while a vigorous attempt on the evaluation of the cognitive, behavioural and psychosocial aspects may be beneficial.